Kompensasi Sebagai Suatu Upaya dalam Memotivasi Karyawan di Universitas 17 Agustus 1945 Banyuwangi - Ni Kadek Yuliandari (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
University of 17 August 1945 Banyuwangi is one of the universities in Banyuwangi Regency. Being a private university, of course, makes the University of 17 August 1945 Banyuwangi to be maximal in providing services to its students. The services provided by the campus certainly do not only refer to the classroom learning provided by the lecturers, but also from the employees who work on campus. In order for employees to be maximal in providing services to students, of course,the first these employees must  be prosperous from the economic side. Based on this, the authors are interested in researching more deeply about how the role of compensation applied by the campus can motivate its employees. This research was conducted using a qualitative approach with interviews as the basis for data collection. Informants in this research amounted to 5 people who have more than 10 years of work experience and are at the level of officials and staff. Based on the results of the research and discussion, it is found that the fair principle and the fair and reasonable principle applied in the compensation system are able to motivate employees at work. The fair principle applied is reflected through the provision of compensation in accordance with the workload and position of the employee. Then, the principle of worth is felt by employees through the opportunity to get a comfortable and calm life because they are able to meet the needs of life in Banyuwangi properly and fairly.